Future Burden of Non-Communicable Diseases Attributable to Overweight in Chile: A Multistate Life Table Modeling Study - De Moraes-Ferrari, G; Fuentes-Honorato, R (BioMed Central Ltd, 2023)
Background: Previous studies have quantified the current burden of diseases attributable to overweight in Chile. However, no study has estimated the attributable burden of overweight in the future. Herein, we estimated the potential impact of different trajectories in the prevalence of overweight on the incidence and mortality from non-communicable diseases (NCDs) in Chilean adults from 2019 to 2030. Methods: A multistate life table modelling was used to estimate the business-as-usual (BAU: if the current rate of increase in BMI persist through the next 11 years; i.e., 0.4% per year from 2003 to 2017) and three counterfactual scenarios (1: the increase rate of overweight is reduced by half; 2: maintanance of the current prevalence of overweight; 3: the prevalence of overweight is reduced by 6.7%) over a 11-year simulation period for burden of NCDs attributable to overweight in Chilean adults aged 20 to 80 years. The model inputs included nationally representative data of body mass index, national official demographic records, NCDs from the Global Burden of Disease study in 2019, and relative risks from a published meta-analysis. Results: If the current trends of increase in overweight are maintained in Chile, approximately, 669 thousand cases and 117 thousand deaths from NCDs will occur from 2020 to 2030. In case the increase rate of overweight is reduced by half during this period, around 7 thousand cases and 1.4 thousand deaths from NCDs would be prevented, while achieving no increase in the prevalence of overweight would avert 10 thousand cases and 2 thousand deaths. In the optimistic scenario of reducing the prevalence of overweight by 6.7% until 2030, approximately 25 thousand cases and 5 thousand deaths from NCDs would be prevented. Conclusion: We estimated that the number of NCDs cases and deaths that could be avoided by decreasing the prevalence of overweight in Chilean adults. Preventive programs aimed to reduce overweight may have a high impact on the future burden of NCDs in Chile. © 2023, The Author(s).